IMPACT OF INTEGRATED SUPERVISION ON VOLUNTARY PENSION INSURANCE EFFICIENCY - Tatjana Rakonjac-Antić; Vesna Rajić (Economic Review)
Adequate supervision (control) of the functioning of voluntary pension insurance is one of the preconditions for the development of this form of insurance. The primary objective of supervision is to protect insured persons and insurance beneficiaries by providing conditions for unhindered and solvent operation of voluntary pension fund management companies. There are three models of supervision in the theory and practice of voluntary pension insurance: integrated, partially integrated, and specialized models of supervision. This paper analyzes the integrated model of supervision, which implies the existence of an institution in charge of the supervision of the functioning of the whole financial sector, including the sectors of banking, insurance, voluntary pension insurance, etc. Some of the variables specific to countries with integrated supervision are presented statistically. The system of voluntary pension insurance in Serbia is still in an early stage, with the integrated model of supervision, implemented by the National Bank of Serbia (NBS).